Acute Pancreas Allograft Rejection Is Associated With Increased Risk of Graft Failure in Pancreas Transplantation. Issue 4 (22nd February 2013) - Dong, M.; Parsaik, A. K.; Kremers, W.; Sun, A.; Dean, P.; Prieto, M.; Cosio, F. G.; Gandhi, M. J.; Zhang, L.; Smyrk, T. C.; Stegall, M. D.; Kudva, Y. C.
<x xml:space="preserve">Abstract</x> The effect of acute allograft rejection (AR) on long‐term pancreas allograft function is unclear. We retrospectively studied 227 consecutive pancreas transplants performed at our institution between January 1, 998 and December 31, 2009 including: 56 simultaneous pancreas and kidney (SPK), 69 pancreas transplantation alone (PTA); and 102 pancreas after kidney (PAK) transplants. With a median follow‐up of 6.1 (IQR 3–9) years, 57 patients developed 79 episodes of AR, and 19 experienced more than one episode. The cumulative incidence for AR was 14.7%, 19.7%, 26.6% and 29.1% at 1, 2, 5 and 10 years. PTA transplant (hazards ratio [HR] = 2.28, p = 0.001) and donor age (per 10 years) (HR = 1.34, p = 0.006) were associated with higher risk for AR. The first AR episode after 3 months post PT was associated with increased risk for complete loss (CL) (HR 3.79, p < 0.001), and the first AR episode occurring during 3‐ to 12‐month and 12‐ to 24‐month periods after PT were associated with significantly increased risk for at least partial loss (PL) (HR 2.84, p = 0.014; and HR 6.25, p < 0.001, respectively). We conclude that AR is associated with increased risk for CL and at least PL. The time that the first AR is observed may influence subsequent graft failure.